How rabies infection occurs - International Livestock Research Institute (International Livestock Research Institute, 2022)
It is essential to seek treatment for rabies immediately after being bitten or scratched by an unvaccinated animal. The virus can take days, weeks or even months to reach the brain - but once it does, it is 100% fatal. The One Health in Africa Centre at ILRI supports the eradication effort against rabies in Kenya through mass dog vaccination campaigns.